Penerapan Bahasa Inggris Dalam Pengajaran Empat Mata Pelajaran Utama Pada Jenjang Sekolah Dasar - Made Suardika Jaya (Edukasi: Jurnal Pendidikan Dasar, 2020)
As a prospective professional teacher in the future, especially with the market demand, the primary school teacher education (PGSD) students have the opportunity to have career in primary schools with academic skills. To be able to improve their overall competency, having English language skills will certainly become good value. Especially, if they later have career at an international standard primary school, delivering material in English language is definitely a challenge. However, it does not mean that it is unable to overcome. There are a variety of tips that students can practise in teaching four main subjects, which are mathematics, natural science, social science and civics or citizenship education in English. The PGSD students must have high motivation to be able to master English language for supporting their careers later, thus they are able to become teachers who are not only capable of teaching subject matters, but can also utilise English language appropriately and accordingly. Keywords: The primary school teacher education, English language, four main subjects